Engineering Conductive Hydrogels with Tissue-like Properties: A 3D Bioprinting and Enzymatic Polymerization Approach - Li, Changbai; Naeimipour, Sajjad; Rasti Boroojeni, Fatemeh; Abrahamsson, Tobias; Strakosas, Xenofon; Yi, Yangpeiqi; Rilemark, Rebecka; Lindholm, Caroline; Perla, Venkata K.; Musumeci, Chiara; Li, Yuyang; Biesmans, Hanne; et al. (WILEY, 2024)
Hydrogels are promising materials for medical devices interfacing with neural tissues due to their similar mechanical properties. Traditional hydrogel-based bio-interfaces lack sufficient electrical conductivity, relying on low ionic conductivity, which limits signal transduction distance. Conducting polymer hydrogels offer enhanced ionic and electronic conductivities and biocompatibility but often face challenges in processability and require aggressive polymerization methods. Herein, we demonstrate in situ enzymatic polymerization of pi-conjugated monomers in a hyaluronan (HA)-based hydrogel bioink to create cell-compatible, electrically conductive hydrogel structures. These structures were fabricated using 3D bioprinting of HA-based bioinks loaded with conjugated monomers, followed by enzymatic polymerization via horseradish peroxidase. This process increased the hydrogels' stiffness from about 0.6 to 1.5 kPa and modified their electroactivity. The components and polymerization process were well-tolerated by human primary dermal fibroblasts and PC12 cells. This work presents a novel method to fabricate cytocompatible and conductive hydrogels suitable for bioprinting. These hybrid materials combine tissue-like mechanical properties with mixed ionic and electronic conductivity, providing new ways to use electricity to influence cell behavior in a native-like microenvironment. This study introduces a novel method to enhance hydrogel conductivity and biocompatibility for biomedical applications. By using in situ enzymatic polymerization of pi-conjugated monomers within a hyaluronan-based hydrogel bioink, followed by 3D bioprinting, the resulting hydrogels exhibit improved stiffness, electroactivity, and cytocompatibility. These conductive hydrogels provide a versatile platform for advanced 3D cell culture and neural engineering.image (c) 2024 WILEY-VCH GmbH

Hydrogels are promising materials for medical devices interfacing with neural tissues due to their similar mechanical properties. Traditional hydrogel-based bio-interfaces lack sufficient electrical conductivity, relying on low ionic conductivity, which limits signal transduction distance. Conducting polymer hydrogels offer enhanced ionic and electronic conductivities and biocompatibility but often face challenges in processability and require aggressive polymerization methods. Herein, we demonstrate in situ enzymatic polymerization of pi-conjugated monomers in a hyaluronan (HA)-based hydrogel bioink to create cell-compatible, electrically conductive hydrogel structures. These structures were fabricated using 3D bioprinting of HA-based bioinks loaded with conjugated monomers, followed by enzymatic polymerization via horseradish peroxidase. This process increased the hydrogels' stiffness from about 0.6 to 1.5 kPa and modified their electroactivity. The components and polymerization process were well-tolerated by human primary dermal fibroblasts and PC12 cells. This work presents a novel method to fabricate cytocompatible and conductive hydrogels suitable for bioprinting. These hybrid materials combine tissue-like mechanical properties with mixed ionic and electronic conductivity, providing new ways to use electricity to influence cell behavior in a native-like microenvironment. This study introduces a novel method to enhance hydrogel conductivity and biocompatibility for biomedical applications. By using in situ enzymatic polymerization of pi-conjugated monomers within a hyaluronan-based hydrogel bioink, followed by 3D bioprinting, the resulting hydrogels exhibit improved stiffness, electroactivity, and cytocompatibility. These conductive hydrogels provide a versatile platform for advanced 3D cell culture and neural engineering.image (c) 2024 WILEY-VCH GmbH
Engineering Conductive Hydrogels with Tissue-like Properties: A 3D Bioprinting and Enzymatic Polymerization Approach
Keywords: 3D printing; cell scaffold; conducting polymer; in vitro; polymerization; 3D printing; cell scaffold; conducting polymer; in vitro; polymerization